Exploring Roles of Stakeholders in Combating Substance Abuse in the DIMAMO Surveillance Site, South Africa - Livhuwani Muthelo; Masenyani Oupa Mbombi; Peter Mphekgwana; Linneth Nkateko Mabila; Inos Dhau; Joseph Tlouyamma; Rathani Nemuramba; Reneilwe Given Mashaba; Katlego Mothapo; Cairo Bruce Ntimana; Eric Maimela (SAGE Publishing, 2023)
Background: The increasing prevalence of substance abuse in rural areas of Limpopo Province is a concern for most stakeholders including the families, South Africa Police Service, and social workers. Combating Substance Abuse requires the active roles of various stakeholders in the rural community, due to limited resources for prevention, treatment, and recovery. Purpose: To report on the roles of stakeholders in tackling Substance Abuse during the awareness campaign conducted in the deep rural community of Limpopo Province, DIMAMO surveillance area. Methods: Qualitative narrative design was adopted to explore the roles of stakeholders in combating Substance Abuse during the awareness campaign conducted in the deep rural community. The population consisted of different stakeholders who play an active role in reducing Substance Abuse. The triangulation method was used for data collection (interviews, observations, and taking field notes during presentations). Purposive sampling was used to select all the available stakeholders who actively combat substance abuse in the communities. Thematic narrative analysis was used to analyze the interviews conducted with and content presented by the stakeholders to generate the themes. Results: The prevalence of Substance Abuse among the youth in the Dikgale community is high with a growing trend of Crystal Meth, "nyaope," and Cannabis(marijuana). The prevalence is worsened by the diverse challenges experienced by the families and stakeholders which impact the strategies targeted to combat Substance Abuse. Conclusion: The findings indicated the need for strong collaborations among the stakeholders (including school leadership) to successfully combat Substance Abuse in rural areas. The findings demonstrated a need for a well-capacitated healthcare services with adequate rehabilitation centers and well-trained healthcare providers for combating Substance Abuse to minimize victim stigmatization.